The breaking news on distribution of the Italian hare (Lepus corsicanus) in Cilento, Vallo di Diano e Alburni National Park - Buglione, Maria; Troiano, Claudia; Petrelli, Simona; De Filippo, Gabriele; Notomista, Tommaso; Maselli, Valeria; Gregorio, Romano; Fulgione, Domenico (BORNH Bulletin of Regional Natural History, 2021)
The Italian hare (Lepus corsicanus) is an endemic species of the Central-Southern Italy and Sicily, classified as vulnerable by the International Union for Conservation of Nature because of the impact of human habitat alterations, the low density and fragmentation of sub-populations and the ecological competition with the European hare (Lepus europaeus), intensively restocked as a game species. The Cilento, Vallo di Diano e Alburni National Park is one of the most important area of occurrence of the Italian hare in Southern Italy, where it live in sympatry with the European hare. However, from 2010 there are no updated information about the distribution of the Italian hare in this important basin. Here, we provide the “breaking news” on its distribution in the National Park using non-invasive genetically validated data. Our findings could give an effective contribution for management strategies aiming at the conservation of this endemism since that the clear knowledge of the distribution pattern of a species is the first stage required in all ecological studies and management planning.